Protection of Children in the African Human Rights System: Framework and Institutions - Mensah, Cocou Marius (Children’s Rights in Regional Human Rights Systems, 2024)
Safeguarding the rights of children remains a fundamental priority in every society. In Africa, a region experiencing the highest fertility rate globally – at 31,599 births per 1,000 people in 2023 – the responsibility to ensure the well-being of its young population is crucial. With approximately 60% of its inhabitants aged below 25 years, Africa’s sizeable youth demographic underscores the pivotal role children play in shaping the continent’s future and driving sustainable development. This chapter delves into the structure of the African human rights system and the organisations that serve as the cornerstone for upholding and advocating children’s rights. It considers the diverse cultural, legal, and societal landscapes across the continent. Furthermore, the chapter examines the rationale underpinning legal mechanisms such as oversight committees designated to safeguard children’s rights. Emphasis is placed on their significance in addressing several pressing challenges confronting children in Africa. Keywords: African Charter on the Rights and Welfare of the Child, Children’s Rights, African Human Rights Mechanism, Youthful Demographics, Safeguarding Minors, Child Welfare